Embolic strokes of undetermined source in a cohort of Polish stroke patients - Bembenek, Jan Pawel (Neurol Sci, 2018)
We aimed to provide a descriptive analysis of embolic stroke of undetermined etiology (ESUS) population based on a long-term prospective stroke registry. We retrospectively analyzed data collected in a detailed registry regarding consecutive patients admitted for first-ever ischemic stroke (IS) between January 2001 and December 2015. We used Org 10172 in Acute Stroke Treatment classification supplemented with ESUS criteria proposed by the Cryptogenic Stroke/ESUS International Working Group. Within the ESUS group, we additionally compared patients ≤ 60 and > 60 years of age. During the study period, there was a total of 3008 (1615 females and 1393 males) admissions of first-ever strokes. The most frequent cause was undetermined (38.7%), followed by cardioembolic (27.7%), large artery atherosclerosis (18.2%), small vessel disease (11.9%), and other determined (3.6%). We identified 326 patients as ESUS, which accounted for 10.8% of all strokes and 28% of strokes of undetermined etiology. ESUS patients were the youngest. Compared to all types of stroke but for those with small vessel disease, ESUS patients were most often independent before stroke and had the least severe neurological deficit at admission and the best outcome at discharge. ESUS patients ≤ 60 years were more frequently independent at discharge than ESUS patients > 60 years. Approximately 11% of patients from our registry met ESUS criteria. ESUS patients were younger when compared to all other stroke etiologies, suffered less severe strokes, and had more favorable outcome at discharge than other groups except for those with small vessel disease strokes.